Pola Hubungan Kepercayaan Dengan Penolakan Imunisasi Dasar Di Wilayah Kerja Puskesmas Tembarak - Wardaya, Elok Cendikia Esti; Martini, Martini; Sutiningsih, Dwi; Hestiningsih, Retno (Jurnal Riset Kesehatan Masyarakat, 2024)
Background: Immunization is a medical process where a person is given a certain vaccine to increase the body's immune response to a particular disease because viruses and bacteria cause many deaths throughout the world. A total of 1.7 million deaths, which contributed 5% to the Indonesian toddler group, are estimated to result in diseases that can be prevented from immunization (PD3I). In 2021, acceptance of complete basic immunization for children under five in Central Java will reach 99% for all types of antigens. However, Temanggung is included in 10 districts that have not achieved the targets set by the Strategic Plan, supported by the occurrence of extraordinary incidents related to measles, diphtheria and hepatitis. The incidence of diseases that can be prevented by immunization in an area is caused by the existence of community groups who have not carried out basic immunization. According to data from the Temanggung District Health Service, there are people who refuse to carry out basic immunizations for babies and toddlers with the main factor being trust. Therefore, further research needs to be carried out regarding the relationship between trust and refusal of immunization in the Tembarak Community Health Center working area. Method: The method used in this research is descriptive observational cross sectional using primary and secondary data Result: The result was that respondents with basic immunization status received more respondents who had supportive beliefs (92.2%) compared to respondents who had unsupportive beliefs, 31.4%) with the chi-square statistical test which showed a p-value <0.001. Conclusion: There is a significant relationship between trust and basic immunization status in children, so solutions such as cross-sector collaboration are needed.